Frequency of Polycystic Ovarian Syndrome in Sub Fertile Gynecology & Obstetrics, Civil Hospital and Dow University of Health & Sciences, Karachi - Noshaba Nafees Abro, Rozina Nargus, Majida Mangi, Shabnam Naz, Reema Samo, Quratulain Shaikh, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the frequency of polycystic ovarian syndrome in sub fertile women. Material and method: This is descriptive study conducted at infertility clinic of Gynecology & obstetrics, civil hospital and Dow University of health & sciences, Karachi for period of 6 months. Total 100 patients was evaluated who were present at infertility clinic were examined for PCOS. Results: Most of the patients were between 21 to 30 years of age. The average age of the patients was 25.5 ± 4.39 years. The most common clinical feature was hirsutism that is observed in 17 percent women. Conclusion: PCOS is a frequent reproductive-age endocrine condition. Biochemical and clinical symptoms vary widely. PCOS should be properly evaluated in all suspected women. Keywords: Polycystic ovarian syndrome, sub-fertility, reproductive-age, endocrine disease